Gröbner Basis in algebras extended by loops (2007)
In this work we extend, to the path algebras context, some results obtained in the commutative context, [2]. The main result is that one can extend the Gr¨obner bases of an ungraded ideal to one possible definition of homogenization for the non commutative case.